FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH (Oryza sativa L) DI DESA TALANG KERING KECAMATAN AIR NAPAL KABUPATEN BENGKULU UTARA - Andriani, Denti; Sarina, Sarina; Asfaruddin, Asfaruddin (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to determine what factors influence the production of lowland rice in Talang Kering Village, Air Napal District, North Bengkulu Regency. In this study, the samples taken were 27 respondents from a total of 80 populations. The data used are secondary data and primary data, the analysis used in this study is Cobb-Douglass and uses SPSS analysis. Cobb-Douglass is a function or equation that involves two or more dependent variables that are explained (Y), and the others are called independent variables that are explained (X). The results of the regression coefficients show that production is influenced by seed (0.50), land area (0.389), fertilizer (0.209), and use of pesticides (0.181) which greatly affect production while labor (-0.043) does not affect rice production.